Meat quality: Impact of various pre-slaughter conditions. (September 2019) - Karabasil, N; Boskovic, T; Vicic, I; Cobanović, N; Dimitrijevic, M; Teodorovic, V
Abstract: Poor animal welfare is a growing issue of concern all over the world. During pre-slaughter phases, some activities, if poorly performed, lead to stress reactions in animals. Animals' responses to a great extent depend on species, breed, sex and age of animal. Food and water deprivation, exposure to unfavourable environmental conditions, improper handling and social mixing are just some indicators of compromised animal well-being. All these detrimental activities lead to the development of carcass and meat quality defects. Among them, important defects are untimely death of animals, body weight loss, carcass damage, and the two major meat quality defects, i.e. pale, soft, exudative (PSE) and dark, firm, dry (DFD) meats. Consumer dissatisfaction results, and with economic and financial losses, producers are placed in a disadvantageous position.